De Novo Mutation in a Rare Case of Neurodegeneration with Brain Iron Accumulation - Narang, Arushi; Pooja, Sadhu; Jadhav, Devika; Tambolkar, Sampada; Chalipat, Shiji; Mane, Shailaja (Journal of Neonatal Surgery, 2025)
Neurodegeneration with brain iron accumulation (NBIA) encompasses rare genetic disorders characterized by iron accumulation in the basal ganglia. Beta-propeller protein-associated neurodegeneration (BPAN) represents an extremely rare X-linked dominant subtype, with only 500 cases reported globally. We present a 5-year-old female with genetically confirmed BPAN, manifesting as early-onset refractory epilepsy beginning at three months of age. The patient exhibited global developmental delay followed by progressive neuroregression starting at age three. Clinical examination revealed microcephaly, distinctive dysmorphic features, and significant neurological impairment including spasticity, dystonia, and cognitive deterioration. Neuroimaging demonstrated cerebral atrophy with characteristic iron deposition in the globus pallidus and substantia nigra. Genetic analysis revealed a de novo mutation in the WDR45 gene, resulting in premature protein truncation.This case represents an atypical BPAN presentation with predominant epileptic encephalopathy rather than the classical movement disorder phenotype. The early onset and severity of symptoms expand our understanding of the clinical spectrum of BPAN. While primarily supportive care remains the mainstay of treatment, this case emphasizes the importance of considering BPAN in the differential diagnosis of early-onset epileptic encephalopathy and highlights the need for comprehensive genetic evaluation in similar presentations